Rubber, Oil Palm and Accumulation in Rural West Kalimantan, 1910s - 2010s - Semedi, Pujo (Paramita: Historical Studies Journal, 2022)
The article argues that social tensions in Indonesian oil palm cultivation have social origins internal to the communities that have adopted oil palm, and it traces some of these origins back across several processes of land conversion. In the early 20th century, the adoption of rubber among West Kalimantan farmers led to the privatization of land tenure and wealth accumulation in the hand of village traders, tokeh, that eventually caused social tension within the community. More money has come to the farmers following the conversion of land from rubber to oil palm since the 1990s, and the money is accompanied by a quicker pace of land accumulation in the hands of the village rich and plantation companies. This process opens a path for the grow of local, village-based capitalism.Artikel ini menyampaikan bahwa ketegangan sosial berkaitan dengan budidaya sawit di Indonesia bersumber dari dari dinamika sosial  di dalam masyarakat petani saat mereka mengadopsi tanaman pasar ini. Pada awal abad ke-20, adopsi karet di kalangan petani Kalimantan Barat menyebabkan privatisasi penguasaan tanah dan penumpukan kekayaan di tangan pedagang desa, tokeh, yang akhirnya menimbulkan ketegangan sosial di dalam masyarakat. Uang  dalam jumlah yang lebih besar diterima para petani setelah mereka mengganti karet dengan sawit sejak tahun 1990-an. Kedatangan uang tersebut dibarengi dengan laju akumulasi tanah yang lebih cepat di tangan orang-orang kaya desa dan perusahaan perkebunan. Proses ini membuka jalan bagi tumbuhnya kapitalisme lokal berbasis pedesaan.Cite this article: Semedi, P. (2022). Rubber, Oil Palm and Accumulation in Rural West Kalimantan, 1910s - 2010s. Paramita: Historical Studies Journal, 32(1), 33-44. http://dx.doi.org/10.15294/paramita.v32i1.29470